Prognostic relevance of global work index and global constructive work in patients with non-ischemic dilated cardiomyopathy - Chen, Peng; Aurich, Matthias; Greiner, Sebastian; Maliandi, Gabriele; Müller-Hennessen, Matthias; Giannitsis, Evangelos; Meder, Benjamin; Frey, Norbert; Pleger, Sven Torsten; Mereles, Derliz (The international journal of cardiovascular imaging, 2024)
Myocardial work (MW) derived from pressure-strain loops is a novel non-invasive tool to assess left ventricular (LV) function, incorporating global longitudinal strain (GLS) by speckle tracking echocardiography and non-invasively assessed blood pressure. Studies on the role of MW in dilated cardiomyopathy (DCM) are still limited. Therefore, the aim of this study was to evaluate the potential value of MW for predicting adverse outcomes in patients with DCM. 116 consecutive patients with DCM who underwent heart catheterization were retrospectively recruited from June 2009 to July 2014. 34 patients (30%) met the composite endpoints for major adverse cardiac events (MACE) of cardiac transplantation, need for implantable cardioverter-defibrillator (ICD) therapy, heart failure hospitalization and all-cause mortality. Patients with DCM were followed up for a mean of 5.1 years (IQR: 2.2-9.1 years). Global work index (GWI) and global constructive work (GCW) were not only independent predictors but also provided incremental predictive values (Integrated discrimination improvement [IDI] > 0) of MACE in multivariate Cox models. Furthermore, Patients with GWI < 788 mm Hg% (HR 5.46, 95%CI 1.66-17.92, p = 0.005) and GCW < 1,238 mm Hg% (HR 4.46, 95%CI 1.53-12.98, p = 0.006) had higher risks of MACE. GWI and GCW assessed by strain imaging echocardiography may have an additional value beyond LV-EF and GLS for predicting adverse outcomes in DCM.
Gesehen am 04.11.2024